2019
DOI: 10.3892/ijo.2019.4806
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of a novel cell line (cc‑006cpm8) of moderately/poorly differentiated colorectal adenocarcinoma derived from a primary tumor of a patient

Abstract: In the present study, the cc-006cpm8 novel colon cell line was established from a sample of right colorectal adenocarcinoma obtained from a woman with liver metastasis. It was possible to culture this cell line for ≥100 passages in vitro with vigorous growth. Morphologically, the cells grew as several layers with tight adhesion to the surface of the culture plate. The morphological, immunological and ultrastructural features of these cells suggested their epithelial origin. The characterization of this cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…It has been reported that MUC19 expression is involved in the pathogenesis of Sjogren syndrome and breast cancer; and breast cancer patients with higher MUC19 expression exhibited worse prognosis (23). In addition, MUC19 mutation was found in inflammatory bowel disease, melanoma, colorectal adenocarcinoma, and esophageal squamous cell carcinoma (24)(25)(26)(27). At present, what we understand regarding MUC19 is limited, and the role of MUC19 in lung cancer also remains unclear.…”
Section: Association Of Muc19 Mutation With Immune Responses and Clinmentioning
confidence: 99%
“…It has been reported that MUC19 expression is involved in the pathogenesis of Sjogren syndrome and breast cancer; and breast cancer patients with higher MUC19 expression exhibited worse prognosis (23). In addition, MUC19 mutation was found in inflammatory bowel disease, melanoma, colorectal adenocarcinoma, and esophageal squamous cell carcinoma (24)(25)(26)(27). At present, what we understand regarding MUC19 is limited, and the role of MUC19 in lung cancer also remains unclear.…”
Section: Association Of Muc19 Mutation With Immune Responses and Clinmentioning
confidence: 99%